Peran Pendidikan Agama Kristen dalam Menanamkan Etika Kristen Bagi Generasi Alpha dalam Bermedia Sosial - Agus Arda Setiawan Telaumbanua; Desmeni Telaumbanua; Mesra Cani Putri Daeli; Marchel Anthony Leiwakabessy (REAL DIDACHE: Journal of Christian Education, 2026)
Generation Alpha inhabits a digital ecosystem in which social media is not merely a communication tool but the primary arena for identity formation, social learning, and moral negotiation. Yet this very condition of immersion has given rise to ethical crises such as cyberbullying, identity fragmentation, exposure to pornographic and violent content, and an ongoing erosion of spiritual values. Although scholarship on Christian Religious Education (CRE) and digital formation is growing, existing studies tend either to examine pedagogical models that gesture toward concrete Christian ethical content without specifying it, or to describe social media phenomena without constructing an ethical framework grounded in biblical texts. This study addresses that gap by building a biblical-ethical framework from four normative texts, namely Colossians 4:5 on wisdom as a way of life, Proverbs 2:5 on the fear and knowledge of God, Matthew 5:13–14 on being salt and light in the world, and Galatians 5:22–23 on life according to the fruit of the Holy Spirit. It further explicates how each norm can be concretely implemented in CRE curriculum and practice for Generation Alpha. Drawing on qualitative methods grounded in hermeneutical analysis, this study demonstrates that the four ethical dimensions are not only theologically coherent but also pedagogically actionable. Accordingly, CRE serves as a strategic normative agent in instilling Christian ethics and shaping the digital character of Generation Alpha, equipping them with a moral compass for responsible and Christlike engagement in digital spaces. Keywords: christian ethics; christian religious education; digital character formation; generation alpha; hermeneutical analysis Abstrak Generasi Alpha menghuni ekosistem digital di mana media sosial bukan sekadar alat komunikasi, melainkan arena utama pembentukan identitas, pembelajaran sosial, dan negosiasi moral. Namun justru kondisi imersi inilah yang melahirkan krisis etika seperti perundungan siber, fragmentasi identitas diri, paparan konten pornografis dan kekerasan, serta pengikisan nilai-nilai spiritual secara berkelanjutan. Meskipun kajian tentang Pendidikan Agama Kristen (PAK) dan formasi digital semakin berkembang, penelitian yang ada umumnya hanya mengkaji model pedagogis yang mengarah kepada konten etika Kristen yang konkret, atau sekadar mendeskripsikan fenomena media sosial tanpa membangun kerangka etis yang berpijak pada teks Alkitab. Penelitian ini mengisi celah tersebut dengan mengonstruksi kerangka etika alkitabiah dari empat teks normatif, yaitu Kolose 4:5 tentang kebijaksanaan sebagai gaya hidup, Amsal 2:5 tentang takut dan mengenal Tuhan, Matius 5:13-14 tentang menjadi garam dan terang dunia, serta Galatia 5:22-23 tentang hidup menurut buah Roh Kudus. Penelitian ini juga menjelaskan bagaimana setiap norma dapat diimplementasikan secara konkret dalam kurikulum dan praksis PAK bagi Generasi Alpha. Dengan menggunakan metode kualitatif berbasis analisis hermeneutis, penelitian ini membuktikan bahwa keempat dimensi etika tersebut tidak hanya koheren secara teologis, tetapi juga dapat dioperasionalkan secara pedagogis. Dengan demikian, PAK berperan sebagai agen normatif yang strategis dalam menanamkan etika Kristen dan membentuk karakter digital Generasi Alpha, sehingga mereka mampu berinteraksi di ruang digital secara bertanggung jawab dan berkarakter Kristiani. Kata Kunci: analisis hermeneutis; etika Kristen; formasi karakter digital; generasi alpha; pendidikan agama Kristen